Agent-based modeling of adoption investing decisions - Solodukhin, Stanislav V.; Shaitanova, Eugenia S. (Journal of the Belarusian State University. Economics, 2019)
The analysis of the current financial market is held. The addiction between behavioral characteristics of market participants and the reaction of market indicators is revealed. The necessity of attention to the behavioral aspect of decision making in the management of economic objects is substantiated. The methodology of economics and mathematical modeling, which is the basis of the concept of forming an economic-mathematical model of management of investment resources of the enterprise, allows us to carry out an analysis of the processes of functioning of the investment activity of the enterprise, as well as to formalize the processes of optimization and planning of investment resources at the enterprise.
Keywords: investment operation; agent-oriented model; financial market; decision making; herding behavior; behavioral economics